Design and Analysis of Three Phase Axial Flux Permanent Magnet Machine with Different PM Shapes for Electric Vehicles - Ziaul Islam; Faisal Khan; Basharat Ullah; Ahmad H. Milyani; Abdullah Ahmed Azhari (Energies, 2022)
Axial flux permanent magnet (AFPM) machines are good candidates for electric vehicle applications due to their high torque density, improved efficiency, and better flux distribution; thus, they are often used. A dual-rotor single-stator AFPM machine with four differently shaped permanent magnet (PM) rotors is investigated. The main aim of this paper is to enhance the average torque while minimizing the cogging torque and torque ripples at the expense of low PM volume. The proposed machines are analyzed in terms of flux linkage, back-EMF, cogging torque, average torque, and torque ripples. The analysis reveals that the machine with an arc-shaped PM rotor performs better than the others. In addition, the trapozoidal arc-shaped PM used in the AFPM machine outperforms the hexagonal, skew arc, and traditional trapezoidal PMs. The torque density of the trapezoidal-shaped PM machine is 40.23 (KNm/<semantics>m3</semantics>), while that of the hexagonal shape is 32.46 (KNm/<semantics>m3</semantics>), that of the skew arc shape is 39.78 (KNm/<semantics>m3</semantics>), and that of the arc shape is 50.38 (KNm/<semantics>m3</semantics>).